L'Assistance maternelle de Montréal (1912-1961): un exemple de marginalisation des bénévoles dans le domaine des soins aux accouchées - Baillargeon, Denyse (Dynamis, 1999)
Keywords: Assistance maternelle; Femmes

Making Do: Women, Family, and Home in Montreal during the Great Depression - Baillargeon, Denyse (Wilfrid Laurier University Press, 1999)
Translators: _:n32037
Keywords: Crise; Famille; Femmes

La colocation comme situation de communication interculturelle, le discours de cinq jeunes français vivant avec des québécois - Ferrand, Nathalie (Université du Québec à Montréal, 1999)
Keywords: Français; Locataires; Logement

La philanthropie et la violence maritale. Le cas de la Montreal Society for the Protection of Women and Children et de la Woman's Christian Temperance Union of the Province of Quebec - Hébert, Fernand (Université du Québec à Montréal, 1999)
Keywords: Enfants; Famille; Femmes; Philanthropie

Portrait multidimensionnel de la pauvreté sur l'île de Montréal: une étude de la précarité et de la subsistance à partir des données du recensement de la population (1986 et 1996) - Julien, Frédéric (Université de Montréal, 1999)
Keywords: Pauvreté

"This is our Work": The Women's Division of the Canadian Department of Immigration and Colonization, 1919-1938 - Mancuso, Rebecca (Université McGill, 1999)
Anglophone women, working in a new capacity as federal civil servants, exercised a significant influence on Canadian immigration policy in the interwar years. This dissertation focuses on the women's division of the Canadian Department of Immigration and Colonization, an agency charged with recruiting British women for domestic service from 1919 to 1938. The division was a product of the women's wing of the social reform movement and prevailing theories of gender difference and anglo-superiority. Tracing its nearly twenty years of operations shows how the division, initially regarded as a source of imperial strength and a means of English Canada's cultural survival, came to symbolize the disadvantages of Canada's connection to Great Britain and supposed weaknesses inherent in the female character. This institutional study explores the real and imagined connections among gender, imperialism, and the changing socio-economic landscape of interwar Canada. Lien avec Montréal - dans la thèse
Keywords: Femmes; Fonctionnaires

Rethinking Juvenile Prostitution: Insights from Youths on the Street - Morris, Jason (Université McGill, 1999)
Keywords: Enfants; Prostitution

The Homeless, the Whore, the Drunkard, and the Disorderly: Contours of Female Vagrancy in the Montreal Courts, 1810-1842 - Poutanen, Mary Anne (Gendered Pasts: Historical Essays in Femininity and Masculinity in Canada, 1999)
Keywords: Délinquance; Femmes; Itinérance; Prostitution

Étude sur l'évolution d'enfants âgés de 6 à 12 ans et de leur famille suivis par les services externes des centres de réadaptation pour jeunes en difficulté d'adaptation des Centres jeunesse de Montréal - Touchette, Luc (Université de Sherbrooke, 1999)
Keywords: Enfants

La robe montréalaise bourgeoise, 1870-1883: clichés, tendances et contextes de consommation - Vallières, Nicole (Université Laval, 1999)
Keywords: Bourgeoisie; Vêtements